2012
DOI: 10.1074/jbc.m112.394270
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Mechanism of the LY6K Gene Expression in Human Breast Cancer Cells

Abstract: Background: LY6K is a candidate cancer biomarker that promotes invasion and metastasis. Results: AP-1 activation is required for the LY6K expression and interfered by SNP242 or methylation. Conclusion: AP-1 promotes LY6K expression that regulates cell mobility, whereas SNP242 or methylation reduces the metastasis. Significance: Understanding the regulatory mechanisms of the LY6K is important for investigating breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In addition, LY6K expression is downregulated by ectopic expression of ERα (Figure 1E and 1F). It was reported that highly upregulated LY6K is related to cell proliferation and metastatic abilities in breast cancer [10]. These findings suggested that ERα could be involved in attenuating metastatic and proliferative capacities and may enhance drug sensitivities in ERα-negative breast cancer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, LY6K expression is downregulated by ectopic expression of ERα (Figure 1E and 1F). It was reported that highly upregulated LY6K is related to cell proliferation and metastatic abilities in breast cancer [10]. These findings suggested that ERα could be involved in attenuating metastatic and proliferative capacities and may enhance drug sensitivities in ERα-negative breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, LY6K was reported to be a molecular biomarker in breast cancer [7], bladder cancer [8] and esophageal squamous cell carcinomas [9]. In addition, LY6K expression is regulated by the AP-1 transcription factor that promotes cell proliferation, invasive and metastatic abilities in breast cancer cells [10]. Nonetheless, there are few studies to supporting the effect of LY6K on various type of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all validated targets contained complementarity to the mivaRNAs in their 3 -UTRs (Bellutti et al, 2015). Both microarray and RISC immunoprecipitation approaches also identified the cell-growth protein lymphocyte antigen 6 complex (Aparicio et al, 2010;Bellutti et al, 2015), a protein implicated in both breast, and head and neck cancers (de Nooij-van Dalen et al, 2003;Kong et al, 2012), as a target of 3 -mivaRNAs. Though an increasingly large body of work is focused upon mivaRNA target identification, another layer of complexity is added by the finding that not all AdV small RNAs originate from VA RNAs (Zhao et al, 2013).…”
Section: Dicer Saturationmentioning
confidence: 92%
“…Immunoblotting was carried out according to a previously described method using anti-LY6K (I-14; Santa Cruz Biotechnology, Santa Cruz, CA, USA) and anti-β-actin (Bethyl Laboratories, Inc. Montgomery, TX, USA) antibodies [23]. …”
Section: Methodsmentioning
confidence: 99%